2003
DOI: 10.1017/s1014233900001590
|View full text |Cite
|
Sign up to set email alerts
|

Genetic base and inbreeding of Canadienne, Brown Swiss, Holstein and Jersey cattle in Canada

Abstract: SummaryThe narrowing of the genetic base is of major concern to many cattle breeders and this is a consequence of a small effective population size and an increase in the inbreeding coefficient in cattle populations. Studies of pedigrees of cattle populations found in Canada showed that the effective population size and rate of inbreeding over a 12-year period (1983–94) were 123 and 0.412 percent for Canadienne, 975 and 0.054 percent for Brown Swiss, and 2 183 and 0.024 percent for Jersey cattle populations. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous studies have showed a wide interval frequency of K and A allelic variants K (0.37) and A (0.63) (Grisart et al, 2002;Gautier et al, 2007); K (0.25) and A (0.75) (Fontanesi et al, 2007); K (0.59) and A (0.41) (Patel et Fixation index in Holstein population (Table 1) indicate inbreeding, probably as results of long term using advanced breeding technologies and the proliferation of a small group of closely related sires. Hansen et al (2003) report that only 10 bulls of their respective breed sired 61 % of the Canadian, 21 % Brown Swiss, 29 % Jersey cattle populations, and 41 % of the Holstein bulls in the bull studs. More and more breeders are demanding proven sires to increase milk production from fewer cows resulting in slow but expected decreasing level of genetic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have showed a wide interval frequency of K and A allelic variants K (0.37) and A (0.63) (Grisart et al, 2002;Gautier et al, 2007); K (0.25) and A (0.75) (Fontanesi et al, 2007); K (0.59) and A (0.41) (Patel et Fixation index in Holstein population (Table 1) indicate inbreeding, probably as results of long term using advanced breeding technologies and the proliferation of a small group of closely related sires. Hansen et al (2003) report that only 10 bulls of their respective breed sired 61 % of the Canadian, 21 % Brown Swiss, 29 % Jersey cattle populations, and 41 % of the Holstein bulls in the bull studs. More and more breeders are demanding proven sires to increase milk production from fewer cows resulting in slow but expected decreasing level of genetic diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the quality of frozen-thawed sheep and goats' spermatozoa is very poor, forcing researchers and farmers to prefer sexing fresh semen, which requires stations to be in closer proximity to the farms. It also appears that this technology requires a high selection intensity for good quality traits, hence purchasing sex-sorted semen from the nearby station can increase the chances of genetic base and inbreeding ( 58 ). Therefore, this review also examines the limitations of sexing semen and focuses on fertility outcomes after the utilization of sex-sorted semen and different artificial insemination techniques, pregnancy and embryonic loss following the use of sex-sorted semen, the proteomic shift in sexed semen and its influence, impaired sperm protection, and the decline in the antioxidant level (total superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and glutathione reductase) in the semen following sexing semen.…”
Section: Limitations Associated With Sexed Semenmentioning
confidence: 99%